Molecular dynamics simulation study on the mechanism of nanoparticle dispersion stability with polymer and surfactant additives - Xu, Na; Lv, Yaodong; Zhang, Laiqiang; Zhang, Shiwen; Li, Xin; Liu, Fei; Li, Zixuan; Zhang, Wei (Chemical engineering science, 2024)
[Display omitted] •Self-assembly characteristics of nanoparticle, polymer and surfactant are studied.•Molecular dynamics mechanism of Coulomb, vdW and hydration effects is analyzed.•An electric triple layer structure for self-assembly aggregate is established.•The attraction layer in Gouy-Chapman-Stern + ion-attraction model is explained. Research on dispersion and stability of nanoparticles in liquid media is one of the key subjects for nanomaterial utilization. Coarse-grained molecular dynamics simulations are carried out to research the self-assembly behaviors of the nanoparticles, PEO (polyethylene oxide) and OTAC (octadecyltrimethylammonium chloride) compound solution system, so as to explore the mechanism of nanoparticle dispersion stability with PEO and OTAC additives. It shows that nanoparticles influence and participate the self-assembly process of PEO and OTAC molecules mainly by electrostatic interactions. In the formation of nanoparticle-PEO-OTAC aggregate, the electrostatic potential plays a controlling role, while the van der Waals potential and hydration effect mainly stabilize and regulate the local connections between different individuals so as to balance the electrostatic potential. An electric triple layer (inner layer-coordinating adsorption layer-diffusion layer) structure is formed in the nanoparticle-PEO-OTAC aggregate, wherein the coordinating adsorption layer is essentially the secondary coordinating adsorption of individuals to the inner layer.